2021
DOI: 10.3390/ijerph18073791
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise and Health-Related Quality of Life in Office Workers: A Systematic Review and Meta-Analysis

Abstract: Office workers are at high risk for many chronic diseases, lowering their health-related quality of life (HRQOL). This systematic review and meta-analysis aimed to summarize the effects of physical exercise on HRQOL in office workers with and without health problems using data obtained from randomized controlled trials (RCTs), quasi-experimental, and observational studies. We searched PubMed, Web of Science, Scopus, Cochrane Library, and several grey literature databases, and identified 26 relevant studies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 56 publications
(216 reference statements)
8
39
0
1
Order By: Relevance
“…In comparison, the EC 100% group improved in PCS with a moderate ES (0.56). Our results agreed with those found in the review conducted by Nguyen et al [42], in which most of the randomized control trials conducted in healthy office workers reported no differences in HRQoL scores.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison, the EC 100% group improved in PCS with a moderate ES (0.56). Our results agreed with those found in the review conducted by Nguyen et al [42], in which most of the randomized control trials conducted in healthy office workers reported no differences in HRQoL scores.…”
Section: Discussionsupporting
confidence: 93%
“…In this scenario, Labour Gymnastics will be carried out remotely, through digital videoconference tools. Recent reviews investigating the effects of physical exercise on the health of office workers [ 21 , 37 , 38 ] reported the significant and protective effects of physical exercise on musculoskeletal pain symptoms (i.e., neck pain and low back pain) [ 21 , 29 , 38 ], with some studies indicating a significant association between physical exercise and QoL [ 21 , 29 , 31 , 39 ]. Previous reviews focused mostly on office workers with musculoskeletal disorders, the most common work-related chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Improving QoL is, therefore, a challenge for occupational health, not least because the work context is crucial for the development and creation of health promotion actions within the scope of work activity [ 38 , 39 , 41 ]. As far as we know, there are few studies about the effects of exercise intervention on the perception of health-related quality of life in computer workers, but studies of this kind would facilitate more efficient preventive and interventional approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have directly examined the relationship between physical exercise and life satisfaction, a number of studies have examined the positive effects of physical exercise on mental health. For example, moderate physical exercise can promote the improvement of individual psychological regulation ability, reduce the level of depression and anxiety, and can significantly improve the individual’s quality of life ( Kvam et al, 2016 ; Frederiksen et al, 2021 ; Nguyen et al, 2021 ). When individuals are physically healthy, emotionally sound and have a high quality of life, they may also be more satisfied with their current life.…”
Section: Introductionmentioning
confidence: 99%